FACTORS INFLUENCING UTILIZATION OF IMPLANTS AMONG WOMEN OF REPRODUCTIVE AGE AT KAWAALA HEALTH CENTRE IV, KAMPALA DISTRICT. A CROSS-SECTIONAL STUDY - Namuli, Recheal; Banita , Mercy; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2025)
Background Implants are a more effective method of family planning methods as they enable women to control their reproductive lives better and are better options for contraception than other long-term family planning methods. The purpose of this study was to identify the factors influencing the utilization of implants among women of reproductive age at Kawaala Health Centre IV, Kampala District. Methodology The method was a descriptive-cross sectional design that utilized quantitative methods of data collection from a sample size of 30 respondents who were sampled by simple random sampling method using a self-administered questionnaire, and data was analyzed using micro soft office programs and presented in the form of tables, graphs, and pie-charts. Results The majority of 12(40%) were between 18 and 24 years of age, and 17(56.7%) were not employed. Regarding individual factors, 19(63.3%) would wish to have three children to start using an implant, 11(36.7%) had one child, 24(80%) did not know all the information about the implant, and 20(66.7%) did not have an overall decision on the use of implants. Concerning Social and cultural factors, 23(76.7%) mentioned that their husbands did not support the use of implants, 27(90%) mentioned that their husbands had desires to have many children, 26(86.7%) did not get support from their husbands during utilization of family planning, and 18(60%) mentioned that their cultural belief does not support the use of implants. Conclusion Factors identified were lack of knowledge about implants, desire to have more children, lack of overall decision-making, lack of husband support, and cultural beliefs. Recommendations Health workers should develop comprehensive health education programs regarding using of long-acting methods of family planning such as implants.